O14.3 Disparities in access to HIV point-of-care testing: the non-urban canadian context. (14th July 2019) - Gahagan, Jacqueline; Kelly, Debbie; Kielly, Jason
Abstract : Background: Testing for sexually transmitted and blood borne infections (STBBIs), including HIV, is a crucial component of sexual health promotion. Testing can help facilitate timely access to care and treatment for those with a positive test result. Despite the approval of HIV point-of-care-testing (HIV POCT) for use in Canada in 2005, many jurisdictions do not have access to this testing innovation such as the 4 Atlantic provinces and there remain challenges in access in many non-urban settings elsewhere in Canada. Methods: Both qualitative and quantitative data were collected as part of an HIV POCT feasibility study with high risk populations in the largest of the 4 Atlantic Canadian provinces as well as from two scoping reviews on access to and uptake of HIV POCT with reference to Canadian non-urban settings. Together these data were examined using a PESTEL analytic framework for common emergent themes in relation to the policy-relevant factors contributing to why HIV POCT remains challenging to access in non-urban settings, even among populations at enhanced risk of infection. Results: Key emergent themes were mapped using the PESTEL analytic framework and found: perceptions of low risk for HIV among those living outside large metropolitan centres; competing public health priorities and expenditures; lack of national policy direction on testing, and issues of stigma; confidentiality; and loss to follow up in non-urban settings. Conclusion: The current jurisdictional constraints facing Federal, provincial, and territorial governments in relation to policies for testing, including access to STBBI testing innovation such as point-of-care testing, requires greater attention as Canada moves forward with the release of the 'Reducing the Health Impact of STBBIs in Canada by 2030: A Pan-Canadian Framework for Action'. Specifically, greater policy attention and national leadership is needed on the core pillar of STBBI testing in an effort to reach the undiagnosed, particularly in non-urban settings. Disclosure: No significant relationships.